Spur dynamics and almond productivity - Lampinen B.; DeJong T.; Weinbaum S.; Metcalf S.; Viveros M. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
The impacts of nitrogen and water on spur longevity and productivity are being studied in a commercial almond (Prunus amygdalus Batsch) orchard. Treatments consist of high (T1) and moderate (T3) water treatments and high (T2) and moderate (T4) nitrogen treatments. After 2 years of treatment imposition, canopy light interception was significantly lower in T2, T3 and T4 compared to T1. 'Nonpareil' yields were significantly lower in T2, T3 and T4 in 2002, but when yield per unit of midday light intercepted was calculated, yield for T3 was not significantly different from yield for T1. Internal canopy spurs have tended to have higher leaf specific areas and lower flowering than more exposed spurs in all treatments. By the end of the 2002 season, T3 and T4 had significantly lower leaf specific area on spurs at mid and inner canopy positions compared to T1.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)